2019
DOI: 10.3390/toxins11100613
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Shiga Toxin-Producing Escherichia coli O157 in the Province of Alberta, Canada, 2009–2016

Abstract: Shiga toxin-producing Escherichia coli (STEC) infections are the product of the interaction between bacteria, phages, animals, humans, and the environment. In the late 1980s, Alberta had one of the highest incidences of STEC infections in North America. Herein, we revisit and contextualize the epidemiology of STEC O157 human infections in Alberta for the period 2009–2016. STEC O157 infections were concentrated in large urban centers, but also in rural areas with high cattle density. Hospitalization was often r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Serotypes reported by this study are commonly detected in animals or animal products ( 66 , 67 ), and linked to animal and human diarrhea ( 68 ) and HUS, under particular conditions ( 69 , 70 ). It is important to highlight that no O157 STEC strains were detected in this study, high morbidity, and mortality serotype linked to animal transmission ( 71 ). The stx subtype genes profile detected in this study, is consistent with that reported previously for most STEC isolates, both in animals from intensive farming systems and people ( 7 , 72 ).…”
Section: Discussionmentioning
confidence: 82%
“…Serotypes reported by this study are commonly detected in animals or animal products ( 66 , 67 ), and linked to animal and human diarrhea ( 68 ) and HUS, under particular conditions ( 69 , 70 ). It is important to highlight that no O157 STEC strains were detected in this study, high morbidity, and mortality serotype linked to animal transmission ( 71 ). The stx subtype genes profile detected in this study, is consistent with that reported previously for most STEC isolates, both in animals from intensive farming systems and people ( 7 , 72 ).…”
Section: Discussionmentioning
confidence: 82%
“…Stx2 is classified into at least 7 subtypes (Stx2a to Stx2g) based on their amino acid sequence diversity [ 34 ]. Among these subtypes, epidemiological data indicate that Stx2a and/or Stx2c producers were more frequently associated with HC and HUS cases [ 20 , 34 ]. Therefore, Stx2 subtyping is important since it may provide valuable information about the virulence of STEC strains.…”
mentioning
confidence: 99%
“…Future treatments for hemolytic uremic syndrome (HUS) would combat bacterial virulence factors instead of passively treating kidney failure, as discussed in a review of mechanisms of EHEC virulence [4]. The lack of progress in EHEC treatments was illustrated from work showing a decline in EHEC infections since the 1980s in the Province of Alberta, Canada, even though HUS still occurs in 5% of infections [5]. This lack of change in HUS incidence over time may also be influenced by changes in dominant EHEC strains.…”
mentioning
confidence: 99%